Partisipasi Masyarakat Desa di Desa Tumbang Manjul dalam Pilgub 2015 Kalimantan Tengah - Eldi Wira Putra (CV. Ulil Albab Corp, 2022)
Community participation in politics is an individual or group activity to be able to play an active role in political life, by exercising their right to choose directly or indirectly the candidate for leader who will run the government. This study uses a qualitative descriptive method. The results of the study show that the participation of the village community in the village of Tumbang Manjul in the 2015 Central Kalimantan gubernatorial election, it can be said that it is very good seeing from the existing data that more than 50% of the people of Tumbang Manjul use their voting rights properly. But besides that, the community still holds a political system of kinship or nepotism which chooses based on kinship relations not based on the capacity of potential leaders.